Effect of Infilled Walls On The Performance of Steel Frame Structures - Mohammadhasani, M.; Hakim, S. J. Seyed; Jameel, M.; A. F., Kamarudin; S. N., Mokhatar; Budiea, A. M. A. (Penerbit UTHM, 2023)
Today, the subject of a building's resistance to lateral loads is one of the most important concerns of structural engineers. The partitions and infilled walls are non-structural elements that are important due to their effects on the lateral resistance of the building frame. Recently, it has been observed that great damage is occurring to infilled walls, partitions, and buildings in an earthquake-prone area. Infilled walls are effective at increasing the hardness and resistance of building frames, which changes the seismic properties of structures. Therefore, the study of interactions between the structural frame and the infilled walls is essential for a better understanding of structural behaviors. In this paper, the effect of infilled walls is investigated on the behaviour of steel frames using ABAQUS software. Modeling is carried out for different types of infilled materials, including brick and panel, as well as different thicknesses of the infills. It was observed that with an increase in the thickness of infills from 7 to 20 cm, the final capacity and energy absorption increased by 78%. Also, the panel-infilled frames have 18% more capacity and 3.8% more energy absorption than the brick-infilled frame in the same full state. As a result, panel-infilled frames outperform brick-infilled frames in terms of performance